Adaptive Leadership and Evidence-Based Policy in Hospital Financial Crisis Management During Disruption: A Systematic Review and Meta-Analysis - Katerine Katerine; Siswanto Pabidang (HM Publisher, 2026)
Hospital financial resilience during crises requires adaptive leadership—the capacity to diagnose complex system challenges and mobilise sustained organisational change. Systematic evidence on adaptive leadership effectiveness in hospital crisis management remains fragmented. Objectives: To synthesise quantitative evidence on the effectiveness of adaptive leadership interventions for improving hospital organisational performance during financial and operational disruptions. Systematic review with meta-analysis using the PRISMA 2020 framework. We searched PubMed, ScienceDirect from 2017–2026 for studies examining adaptive leadership or resilience outcomes in hospital settings during financial or operational crises. Two independent reviewers extracted data and assessed risk of bias using Newcastle-Ottawa Scale (NOS). We estimated effect sizes (Hedges g) from 6 of 7 studies with estimated correlation coefficients (inter-rater reliability ICC=0.85), converted via d = 2r/√(1−r²). Random-effects meta-analysis used DerSimonian-Laird estimator. Certainty of evidence assessed via GRADE. Seven studies (k=7) contributed to meta-analysis; 10 to systematic review. Pooled standardised mean difference (SMD) = 0.467 (95% CI: 0.305–0.628, p<0.0001); I²=0% (Q=1.01, p=0.985). Effect remained robust in sensitivity analyses (leave-one-out: 0.445–0.493). Heterogeneity by study design minimal (Review k=3 SMD=0.476; Empirical k=2 SMD=0.438). GRADE assessment: moderate certainty (downgraded for indirectness and effect size estimation). In conclusion, adaptive leadership interventions show small-to-moderate evidence-supported effect on hospital organisational performance during crises. This effect persists across study designs and contexts despite methodological heterogeneity. This meta-analysis provides initial quantitative synthesis to guide hospital policy-makers and clinical leaders in crisis management strategy selection.